Stand factors related to sensory defects of cork planks - Veloso,Sandra (2015)
Wine bottle stoppers are the main bio-technological product obtained from cork. The 2,4,6-trichloroanisole (TCA) is considered the main responsible for “cork taint” in bottled wines. This study intent to prove the relation between TCA and mancha amarela-yellow spot (MA) and to identify field factors that can be related to the cork TCA presence. Cork planks with and without MA were collected from cork oak stands in ten different regions of the country and 15 variables were analyzed. Three samples were taken from each plank for TCA quantification. The results show that TCA and MA are significantly related and that the TCA level is higher in cork samples coming from stands with shrubs in the understorey.